SAT0447 Safety, Tolerability and Pharmacokinetics of Abt-981, an IL-1A and IL-1β Dual Target Biologic Drug in Development for Osteoarthritis, following Single Dose Administration in Healthy Subjects. (10th June 2014) - Goss, S.; Wang, S.; Klein, C.; Medema, J.; Awni, W.
Abstract : Background: Interleukin-1 (IL-1) plays an important role in the development and progression of osteoarthritis (OA) through stimulating inflammatory mediators, increasing cartilage degradation processes, as well as inhibiting chondrocyte repair of degraded cartilage extracellular matrix. ABT-981 is a novel dual-variable domain immunoglobulin (DVD-Ig™) targeting both IL-1α and IL-1β. Preclinical proof of concept studies demonstrated that simultaneous neutralization of mouse IL-1α and IL-1β confers beneficial effects in mouse OA models over inhibiting either cytokine alone. Objectives: To assess the safety, tolerability, pharmacokinetics (PK), and anti-drug antibody (ADA) assessment of ABT-981 following a single dose in healthy subjects. Methods: The First in Human, Phase 1 study was a randomized, double-blind, placebo-controlled study designed to assess ABT-981 following a single intravenous (IV) infusion (0.3, 1, 3 or 10 mg/kg) or a single subcutaneous (SC) injection (0.3, 1 or 3 mg/kg). Fifty-six male and female healthy volunteers, 18 to 55 years old, enrolled in this study. In each dose cohort, six subjects received active drug and two received placebo. Safety assessment and PK/ADA samples were collected for 84 days following dosing. Results: ABT-981 Cmax and AUC∞ increased in an approximately dose-proportional manner after single dose administration from 0.3 mg/kg to 10 mg/kg IV and 0.3 mg/kg to 3 mg/kg SC. The mean Tmax after SC dosing was approximately 5 days, with maximum concentrations sustained up to 10 days. After IV and SC administration, elimination t1/2 ranged from 11.6 to 14.4 days. The estimated relative bioavailability after SC administration was 46%. Measurable ADA titers were detected in 7 subjects on active treatment. There was no difference observed in ADA titer following IV versus SC administration, nor was there a correlation between ADA incidence and dose. No apparent ADA effect on ABT-981 PK was observed. Following IV infusion and SC administration, ABT-981 was well tolerated in healthy subjects. There was no significant difference in adverse event (AE) profile between subjects receiving ABT-981 or placebo. Eleven subjects receiving ABT-981 or placebo had neutrophil data considered potentially clinically significant, and 4 subjects had an AE of neutropenia. There was no clear association of neutropenia with other AEs, including infections. No laboratory abnormalities were linked with infection. Conclusions: ABT-981, which has two target binding domains for IL-1α and IL-1β, exposures increased in an approximately dose-proportional manner after single dose IV and SC administration in healthy subjects. ABT-981 was well tolerated in healthy subjects administered single ABT-981 doses either via IV infusion or SC. This First in Human study supports further investigation of this DVD-Ig™ following multiple doses in an OA population. Acknowledgements: This study was sponsored by AbbVie. AbbVie contributed to the study design, research, and interpretation of data, writing, reviewing, and approving the publication. Disclosure of Interest: S. Goss Employee of: AbbVie, S. Wang Employee of: AbbVie, C. Klein Employee of: AbbVie, J. Medema Employee of: AbbVie, W. Awni Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.4743